Evaluation of child and adolescent psychiatry consultations in a tertiary university hospital - Uran, Pinar; Sertcelik, Mehmet (The European Research Journal, 2017)
Objective. The aim of this retrospective study was to examine referral pathways to department of Child and Adolescent Psychiatry in a tertiary university hospital for consultation-liaison and to identify patterns associated with demographic characteristics of children, referral sources, the presenting problems, diagnoses and the treatments. Methods. The consultation demands from inpatient and outpatient clinics of our hospital between October 2015 and October 2016 were screened retrospectively. Results. Psychiatric consultations were demanded for 263 child and adolescent patients who were treated in inpatient and outpatient units for one-year period. The children consulted were primarily females (52.5%) and who were in 12 or older age group (62%). Children were referred mostly because of mood and anxiety related complaints. Major depressive disorder was the most common diagnosis. Children were referred mostly from the pediatric emergency service. The intensive care, oncology, hematology and endocrinology departments of pediatrics were also the common referral sources. Psychotropic medications were recommended for 22 percent of children. Psychotherapeutic interventions were conducted in approximately half of the children. Conclusions. Pediatricians have to pay an extra attention to female adolescents. Emergency service demands for suicide attempts are higher than the other departments and there is a need for more collaboration with emergency service. Future studies of child and adolescent psychiatry consultants need to be aware of the growing body of literature supporting the biopsychosocial model of understanding the process of adjustment to chronic childhood illness and the experience of hospitalization.